Potensi Patogenik Infeksi Entamoebacoli dengan Komplikasi Syok Sepsis: Sebuah Laporan Kasus Atipikal - Christina Saputera (PT Dexa Medica, 2026)
Background: Entamoeba coli is a commensal protozoan that lives in the human intestinal lumen (nonpathogenic protozoan). There have been no reports of severe Entamoeba coli-related infections in patients with good nutritional andimmune status. The natural phagocytic properties of Entamoeba coli are are contributed to severe infections with rare complications, including septic shock. Diagnosis is generally established by microscopic stool analysis; positive resultsindicate the presence of Entamoeba coli cysts. Case: A 65-year-old female patient with symptoms of colitis, namely abdominal pain, abdominal cramps accompanied by diarrhea 4 hours before coming to the emergency room, the frequencyof diarrhea 6 times per day with watery, greenish yellow stool, accompanied by mucus. Physical examination showed signs indicating septic shock with positive microscopic stool analysis results for Entamoeba coli. Initial management in theform of broad-spectrum antibiotics plus the amebicidal agent metronidazole and comprehensive management of septicshock provided good outcomes in patient without complications. Conclusions: Although categorized as a nonpathogenic protozoan, the phagocytic ability of Entamoeba coli can trigger a severe systemic inflammatory response, including sepsis.High clinical vigilance is required to detect Entamoeba coli in stool examinations, as well as to ensure early diagnosis and appropriate management to prevent serious systemic complications.